Aneurysm Treatment in Acute SAH with Hydrophilic-Coated Flow Diverters under Single-Antiplatelet Therapy: A 3-Center Experience - Lobsien, D.; Clajus, C.; Behme, D.; Ernst, M.; Riedel, C.H.; Abu-Fares, O.; Götz, F.G.; Fiorella, D.; Klisch, J. (American Journal of Neuroradiology, 2021)
BACKGROUND AND PURPOSE: In certain clinical circumstances, dual-antiplatelet therapy can be problematic in patients with acute SAH. In some aneurysms, however, flow-diverting stents are the ideal therapeutic option. We report our experience with ruptured intracranial aneurysms treated with flow diverters with hydrophilic coating (p48 MW HPC and p64 MW HPC) under single-antiplatelet therapy.MATERIALS AND METHODS: Patients were treated with either flow-diverter placement alone or a flow diverter and additional coiling. Due to the severity of the hemorrhage, the potential for periprocedural rehemorrhage, and the potential for additional surgical interventions, a single-antiplatelet regimen was used in all patients.RESULTS: Thirteen aneurysms were treated in 10 patients. The median age was 62 years; 5 patients were male. All had acute SAH due to aneurysm rupture. Four blood-blister, 2 dissecting, and 7 berrylike aneurysms were treated. Seven aneurysms were adjunctively coiled. Eight of the 10 patients received a single-antiplatelet protocol of aspirin, 1 patient was treated with prasugrel only, and 1 patient was treated with tirofiban first and then switched to the aspirin single-antiplatelet protocol. One device-related complication occurred, a thrombosis of an overstented branch. All stents, however, remained open at DSA, CTA, or MRA follow-up.CONCLUSIONS: The implantation of flow diverters with reduced thrombogenicity due to hydrophilic surface coating under single-antiplatelet therapy seems to be an option in carefully selected cases of SAH due to aneurysm rupture.POorally